Molecular insights into heart field-specific cardiomyocyte differentiation - A computational study - Ricco Zeegelaar; Georgios Argyris; Janine N. Post (PLoS ONE, 2026)
Understanding the mechanisms underlying cardiomyocyte (CM) differentiation is essential for the accurate generation of the different types of heart cells in vitro. This study advances current models of CM differentiation by introducing a gene regulatory network (GRN) model that integrates early heart field formation with downstream differentiation of committed cardiomyocytes into atrial and ventricular subtypes. The model is implemented using Boolean logic, enabling qualitative simulation of cardiac regulatory dynamics. Attractor analysis identifies steady states corresponding to first and second heart field derived atrial and ventricular cardiomyocytes. The model reveals the mechanism of WNT and BMP signaling in heart field determination and shows how RA regulation of NR2F2 decisively determines atrial versus ventricular cardiomyocyte cell fate. The model reproduced published knockout and overexpression experiments, and probabilistic simulations estimate differentiation efficiencies under varying signaling inputs. The unified Boolean model provides a foundation for generating heart-field-specific cardiomyocytes with precise atrial or ventricular identities, supporting efforts in directed differentiation and targeted heart cell therapies.